Bible Fragments in the “Sermon on High Days” and the “Sermon for Commemoration of St Thomas the Apostle” by Clement of Ohrid - Кравчук, Денис Валерьевич (Slavistica Vilnensis, 2017)
The texts examined in this paper reveal their origin from a single invariant modeling text. It is characterized by the preferential reference to the Gospel of Matthew, the usage of short exact quotes or quotes with minor changes that is evidence in favor of the use of a written source and determines the basic – didactic – function of the Bible fragments. A total of 10 biblical fragments were found, 8 of them are quotations. The set of fragments obeys to author’s particular intention: an implicit development of the main theological theme. This is facilitated not merely by the cited fragments themselves, but also by their biblical context. The fragments of the Sermon on High Days were adapted in accordance with the objectives and preaching logic. Changes of biblical fragments in the Sermon in Commemoration of Thomas the Apostle were more substantial, which had been caused by borrowings from the modeling text that indicates a more recent origin.